Strategies to Increase Customer Interest by Implementing Digital Marketing at Hello Friends Coffee Shop in South Jakarta - Elfa Setiawan; Elizabeth Monica Frara (Lembaga Layanan Pendidikan Tinggi Wilayah III DKI Jakarta, 2023)
This research was conducted to discover the development of customer interest through social media and find solutions to the obstacles faced. The focus of this research is related to the emergence of a